Perancangan Knowledge Management Penyedia Jasa Layanan Internet (Studi Kasus PT. XYZ) - Anggoro Aryo P. (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2016)
Knowledge management is one of the way to develop and improving human resources. Individuals who are in such an organization are the source who has the knowledge and they are becoming the most valuable asset for an organization. In generally, Knowledge Management focusing on making the rules and make knowledge to be usefull and important, make it become available in everywhere, everytime when its needed. The implementation of the Knowledge Management are very needed to face the bussiness competition, to anticipate the market changes, to improve the respond on action and decision making also to improve the individuals experience in taking the decision in an organization. To implementing the Knowledge Management in PT. XYZ, first we have to know how to design the Knowledge Management so that PT. XYZ can easily to manage all the knowledge at the PT. XYZ’s human resources. So that PT. XYZ is hopefully can improve their capability in their core business as an Internet Services Provider Company, then PT. XYZ can achieve the competitive advantage